2017
DOI: 10.1016/j.biopsych.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Amygdala Neuronal Ensembles Encoding Nicotine-Associated Memories Inhibits Nicotine Preference and Relapse

Abstract: BACKGROUND: Nicotine craving and relapse often occurs after reactivation of nicotine reward memories. We recently developed a memory retrieval–reconsolidation interference procedure in which reactivating nicotine reward memories by acute exposure to nicotine (the unconditioned stimulus [UCS]) and then pharmacologically interfering with memory reconsolidation decreased relapse to nicotine seeking in rats and nicotine craving in smokers. Here, we investigated underlying mechanisms. METHODS: In the first series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 60 publications
4
46
0
1
Order By: Relevance
“…This discrepancy may reflect distinct retrieval paradigms. Indeed, US retrieval has been shown to activate more memory traces and stronger protein alterations than CS retrieval (Liu et al, 2014;Xue et al, 2017;Yuan et al, 2019). Furthermore, we found that the pharmacological inhibition of Pi4KIIa in the BLA decreased GluA1 levels 1 h after US retrieval, and the genetic knockdown of Pi4KIIa impaired the enhancement of mEPSC frequency that was induced by US retrieval, suggesting a regulatory role for Pi4KIIa in GluA1 surface expression and synaptic efficacy in the rat BLA.…”
Section: Discussionmentioning
confidence: 67%
“…This discrepancy may reflect distinct retrieval paradigms. Indeed, US retrieval has been shown to activate more memory traces and stronger protein alterations than CS retrieval (Liu et al, 2014;Xue et al, 2017;Yuan et al, 2019). Furthermore, we found that the pharmacological inhibition of Pi4KIIa in the BLA decreased GluA1 levels 1 h after US retrieval, and the genetic knockdown of Pi4KIIa impaired the enhancement of mEPSC frequency that was induced by US retrieval, suggesting a regulatory role for Pi4KIIa in GluA1 surface expression and synaptic efficacy in the rat BLA.…”
Section: Discussionmentioning
confidence: 67%
“…The training of intravenous heroin self‐administration, extinction training, heroin‐priming‐induced reinstatement, renewal, and spontaneous recovery of heroin‐seeking behaviors are based on previous studies . The heroin operant‐CS retrieval manipulations were identical to the one used in our previous studies . We injected the rats noncontingently with the previously self‐administered drug (UCS) (heroin 0.1 mg/kg, sc) in their homecage .…”
Section: Methodsmentioning
confidence: 99%
“…We performed the stereotactic surgery and implanted 23‐gauge guide cannulas (Plastics One) 1 mm above BLA . For virus injections, the virus construct was injected bilaterally into the BLA based on previous reports .…”
Section: Methodsmentioning
confidence: 99%
“…这些IEG报告品系被用于绘制特定 刺激相关的全脑活性图谱 [67,83,84] 、研究激活类群的电 生理特性 [43,62] 以及通过在体成像揭示集群的功能动态 编码特征 [58,69] , 此外表达LacZ的工具还被用于活性神 经集群的干预, Koya等人 [85] 利用β-gal能够催化前体药 物Daun02转化成具有抑制神经元兴奋作用的柔毛霉 素(daunorubicin)的特性, 将Daun02给予到刺激后的cfos-LacZ大鼠的感兴趣脑区, 从而实现了刺激活化神 经集群的失活(图1A). 应用LacZ-Daun02失活系统, 一 系列研究成瘾药物引发行为敏化 [85] 、渴求 [86~89] 、复 吸 [39,90,91] 等作用机制的工作发表.…”
Section: Caunclassified